School-to-work transition: the case of Spanish NEETs. (9th August 2018) - Vancea, Mihaela; Utzet, Mireia
ABSTRACT: The school-to-work transition in Spain has become much more difficult and extended than before, with many young people today experiencing long periods of temporary employment, unemployment or inactivity. This article investigates the main socio-demographic characteristics of Spanish young people not in education, employment or training (NEETs). It also aims to compare them with their non-NEET counterparts in terms of social capital and family background. Analyses were based on a representative sample, corresponding to the year 2016, of Spanish young individuals ages 18–35 years ( n  = 1.826). All analyses were stratified by gender and age group. Overall, the Spanish NEETs had lower educational levels, were mainly unemployed and married, except for NEETs between 18 and 24 years, who were rather inactive and single. They also experienced previous unemployment, had more unemployed friends, and were coming from poorer family backgrounds in comparison with their non-NEET counterparts.